Sensemaking, meaning-making and practice perspectives in strategic planning for a veteran service nonprofit organization - Metzger, Susan Theresa (Kansas State University, 2021)
The purpose of this research is both practical and scholarly. From a practical perspective, this study’s purpose is to explore the successes and challenges of a veteran service nonprofit organization through an Appreciative Inquiry (AI) process to inform the organization's future priorities and direction. From a scholarly perspective, this research extends organizational literature in that it brings to light the ways members of an organization negotiate roles and navigate tensions in the construction of strategy and the function of the strategic text in inspiring commitment and motivating change. Using a constructivist grounded theory approach, this research builds on the principles and concepts of sensemaking and meaning-making in a community of practice and strategy-as-practice. Data collected from in-depth qualitative fieldwork included interviews, a focus group, an open forum, a facilitated virtual board retreat, observations, correspondence, and archival materials. Data were analyzed using two coding techniques, one for the drafting of the strategic plan and the other an inductive approach to explore the research questions. The preliminary findings reveal three tensions (1) tensions in the transition from top-down to more inclusive strategic planning; (2) tensions between conflict and mutual engagement; and (3) tensions in the relationship between practitioners and strategic objects in creating meaning. Ultimately, this research provides perspectives on the broader implications for engaging leadership communication processes, such as appreciative inquiry, in facilitating organizational change.
Keywords: Strategic planning; Appreciative inquiry; Strategy as practice; Meaning making; Sensemaking; Military veteran nonprofit organizations